Health Literacy of Individuals with Visual Impairments in Yogyakarta Province, Indonesia - Widyakusuma, Niken Nur; Ekasari, Marlita Putri; Wiedyaningsih, Chairun (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Individuals with visual impairments tend to have low health outcomes. Exploring health literacy among this group can provide a basis for designing effective strategies for healthcare services that assist this special population.Objectives: This study aimed to determine the health literacy level of individuals with visual impairments.Methods: A cross-sectional study was employed in this study. We administered a survey using the Health Literacy Scale European Union Q16 (HLS-EU-Q16) Indonesian version questionnaire to individuals with visual impairments in Yogyakarta. Members of two Non-Government Organisations (NGOs), namely Ikatan Tunanetra Muslim Indonesia/Indonesian Muslim Blind association (ITMI) and Persatuan Tuna Netra Indonesia/Indonesian Blind Association (Pertuni) were invited as respondents using a purposive sampling method. Data was collected during the NGOs regular meetings in August and September 2019, which took place in some members’ houses or public places throughout Yogyakarta province.Results: A total of 95 eligible respondents who consented to join the study had a health literacy index of 31.29 ± 8.91, classified as problematic, with an index range between 3.13 and 50.00 (inadequate to excellent).Conclusion: Our findings revealed that individuals with visual impairments have problematic health literacy and face multiple determinants to improve their health literacy. This condition requires pharmacists and other health professionals to be aware of it and to develop an appropriate strategy to deal with it comprehensively.